Elders and Youth Perception of Self-Death Announcement in Nepal - Ghimire, Maya Nath; Mishra, Anjay Kumar (NPRC Journal of Multidisciplinary Research, 2025)
Background: Death perceptions in Nepal are deeply influenced by Hindu philosophical traditions, which view death as a transitional phase where the soul separates from the body and enters a cycle of rebirth. Despite cultural significance, comparative studies on how elders (≥60 years) and youth (14–24 years) perceive self-death announcements remain scarce. Existing literature highlights gaps in systematic documentation of suicide and death attitudes, particularly in low-resource settings like Nepal, where institutional reporting is fragmented and stigmatized. This study addresses these gaps by exploring generational differences in death assumptions, integrating socio-cultural, religious, and health-related factors. Objective: To compare elders’ and youths’ perceptions of self-death announcements in Nepal, focusing on attitudes toward mortality, afterlife beliefs, and contextual factors (e.g., health, family support, and environmental stressors). Methods: A mixed-methods meta-synthesis was conducted in Chitwan, Makawanpur, and Sunsari districts, combining qualitative interviews and quantitative surveys. Purposive sampling included 110 participants (55 elders, 55 youth). Qualitative data were thematically analyzed, while quantitative responses were tabulated for cross-generational comparisons. Questions covered life expectancy assumptions, desired death circumstances, afterlife beliefs, and health practices. Findings: Elders associated death with chronic illnesses (e.g., hypertension, diabetes) and expressed a desire to die in religious settings (e.g., Devghat) to attain Baikuntha (Vishnu’s abode). 81.8% (45/55) believed in rebirth, yet 67.3% (37/55) rejected reincarnation, seeking liberation (Moksha). Youth emphasized environmental stressors (e.g., pesticide-laden food, pollution) as mortality risks. Only 34.5% (19/55) feared death, contrasting with elders (7.3%, 4/55). Over 65% (36/55) youths desired rebirth, often linking it to familial bonds. Novel insights: Elders prioritized ritual purity for a "good death," while youth framed death as uncertain but inevitable, influenced by modernization and declining joint-family systems. Conclusion: Generational disparities reflect Nepal’s socio-cultural shifts: elders adhere to Hindu eschatology, whereas youth integrate pragmatic concerns (e.g., environmental degradation). Findings underscore the need for culturally sensitive death education and policies addressing elder care and youth mental health. Novelty: This study is among the first to juxtapose elder-youth death perceptions in Nepal, blending indigenous Hindu cosmology with contemporary challenges like urbanization and environmental health risks. It highlights how legal myths (e.g., suicide criminalization) and institutional gaps shape death attitudes.